Digital Exclusion and Social Inequity: A Global Narrative Review of Access to Education, Healthcare, and the Digital Economy - Saleh, Munandi; Irwani; Bahrianoor (Sinergi International Journal of Communication Sciences, 2024)
Digital inequality is a growing concern that contributes significantly to socioeconomic disparities in education, healthcare, and economic participation. This narrative review aims to explore the structural and systemic dimensions of digital inequality and its implications for marginalized communities. Literature was sourced from databases including Scopus, PubMed, and Google Scholar using a combination of targeted keywords and Boolean search techniques. Articles were selected based on relevance, methodological diversity, and contextual alignment. The review identifies critical themes, including the impact of unequal digital access on educational attainment, disparities in telehealth usage, and limited economic opportunities in digitally excluded populations. Findings reveal that regions with weak digital infrastructure and low digital literacy consistently report lower educational performance, reduced health engagement, and limited employment prospects. Public policy, infrastructure investment, and digital training emerge as decisive factors that either mitigate or exacerbate these challenges. The discussion emphasizes the necessity of equitable digital policy design, community-based interventions, and collaborative global strategies to ensure inclusive digital development. Despite growing research on digital inequality, gaps remain in longitudinal analysis and intersectional perspectives. This review recommends future studies to adopt multidimensional frameworks to better inform policy and practice. In conclusion, addressing digital inequality is not only a technological necessity but also a social imperative. Bridging the divide is essential for creating a more just, inclusive, and resilient society in the digital era.